Do the mobile-rich get richer? Internet use, travelling and social differentiations in Finland. (January 2016) - Taipale, Sakari
This article investigates the daily travelling practices that are related to mobile-only, fixed-only and combined mobile/fixed use of the Internet, and the social differentiations that are related to these three ways of accessing the Internet. Survey data ( N = 612) collected from Finland in 2011 are analysed. The article shows that mobile-only Internet use is not associated with particularly diverse or frequent daily travelling practices, whereas combined mobile/fixed use is. Mobile-only Internet users are, in fact, in a relatively disadvantaged position – compared with other users, they are more typically unemployed and their household income is lower. The mobility of Internet access as such does not guarantee a safe social position in society. Mobile Internet use must be complemented with fixed use, which brings about more versatile and frequent travelling. The finding suggests that the 'mobile-rich get richer' when it comes to Internet use and daily travelling practices.